2020
DOI: 10.1094/mpmi-05-20-0123-r
|View full text |Cite
|
Sign up to set email alerts
|

Sec-Delivered Effector 1 (SDE1) of ‘Candidatus Liberibacter asiaticus’ Promotes Citrus Huanglongbing

Abstract: Sec-delivered effector 1 (SDE1) from the Huanglongbing (HLB)-associated bacterium Candidatus Liberibacter asiaticus (CLas) was previously characterized as an inhibitor of defense-related, papain-like cysteine proteases (PLCPs) in vitro and in planta. Here we investigated the contributions of SDE1 to HLB progression. We found that SDE1 expression in the model plant Arabidopsis thaliana caused severe yellowing in mature leaves, reminiscent of both CLas-infection symptoms and accelerated leaf senescence. Inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…However, in many citrus producing areas where HLB is endemic or has high incidence, such as Florida, inoculum eradication is largely abandoned (Graham et al 2020). Intriguingly, despite that Las has not been cultured in artificial media, promising advances have been made that might help develop long-term solutions to control HLB, including understanding the virulence mechanisms of Las (Duan et al 2009;Jain et al 2018;Pitino et al 2018;Chen et al 2020;Clark et al 2020;Pandey et al 2020;Pang et al 2020;Thapa et al 2020a;Thapa et al 2020b;Vasconcelos et al 2020), improving Las detection (Kim and Wang 2009;Pagliaccia et al 2017;Pandey and Wang 2019;Gottwald et al 2020), and developing tolerant or resistant citrus varieties using traditional and novel approaches (Jia and Wang 2014;Rawat et al 2015;Deng et al 2019;Jia et al 2019;Jia and Wang 2020). In addition, in HLB-endemic regions, such as Florida, the HLB management focus has shifted to how to improve and sustain the productivity at the presence of HLB.…”
Section: Introductionmentioning
confidence: 99%
“…However, in many citrus producing areas where HLB is endemic or has high incidence, such as Florida, inoculum eradication is largely abandoned (Graham et al 2020). Intriguingly, despite that Las has not been cultured in artificial media, promising advances have been made that might help develop long-term solutions to control HLB, including understanding the virulence mechanisms of Las (Duan et al 2009;Jain et al 2018;Pitino et al 2018;Chen et al 2020;Clark et al 2020;Pandey et al 2020;Pang et al 2020;Thapa et al 2020a;Thapa et al 2020b;Vasconcelos et al 2020), improving Las detection (Kim and Wang 2009;Pagliaccia et al 2017;Pandey and Wang 2019;Gottwald et al 2020), and developing tolerant or resistant citrus varieties using traditional and novel approaches (Jia and Wang 2014;Rawat et al 2015;Deng et al 2019;Jia et al 2019;Jia and Wang 2020). In addition, in HLB-endemic regions, such as Florida, the HLB management focus has shifted to how to improve and sustain the productivity at the presence of HLB.…”
Section: Introductionmentioning
confidence: 99%
“…SDE1 inhibits the enzymatic activity of citrus papain-like cysteine proteases (PLCPs), which regulate multiple processes in plants, including defense against microbial pathogens (Clark et al, 2018). Other studies also suggested that SDE1 contributes to CLas colonization and the development of leaf yellowing symptoms, possibly by promoting premature senescence in citrus (Pitino et al, 2016;Clark et al, 2020). Although, there is no evidence that targeting effectors would lead to CLas suppression, targeting the Sec system could inhibit protein translocation and have a significant effect on CLas virulence and survival.…”
Section: Secretion Systems and Effectorsmentioning
confidence: 99%
“…Meanwhile, SDE1 interacts with DDX3 and down-regulates the expression of DDX3 in HLB-affected yellowing and mottled leaves of citrus, causing HLB typical chlorosis symptoms [ 108 ], which, however, was not observed by Clark and colleagues [ 107 ]. Severe yellowing and senescence signatures were observed in the mature leaves of SDE1-expressing Arabidopsis thaliana lines [ 109 ]. Moreover, SDE1-expressing Duncan grapefruit exhibited hypersusceptibility to C Las [ 109 ].…”
Section: The Interaction Between C Las and Host Plantmentioning
confidence: 99%
“…Severe yellowing and senescence signatures were observed in the mature leaves of SDE1-expressing Arabidopsis thaliana lines [ 109 ]. Moreover, SDE1-expressing Duncan grapefruit exhibited hypersusceptibility to C Las [ 109 ]. The expression of PR genes ( PR1 , PR3 , and PR5 ) and PTI marker genes ( FRK1 , GST1 , and WRKY22 ) was significantly down-regulated after XccA w inoculation in the SDE15-transgenic compared to that in the nontransgenic Duncan grapefruit [ 110 ].…”
Section: The Interaction Between C Las and Host Plantmentioning
confidence: 99%